State estimation and data fusion for multirate sensor networks. (12th May 2015) - Yan, Liping; Jiang, Lu; Xia, Yuanqing; Fu, Mengyin
Summary: This article is concerned with state estimation and data fusion of a linear dynamic system observed by multirate sensors in the environment of wireless sensor networks. The sampling, estimation, and transmission rates in the wireless sensor networks are different. We derive the optimal linear estimation in the centralized, sequential, and distributed forms. A numerical example is given to show the feasibility and effectiveness of the proposed algorithms. Copyright © 2015 John Wiley & Sons, Ltd.